2022
DOI: 10.1055/a-1778-4002
|View full text |Cite
|
Sign up to set email alerts
|

Early Renin Recovery After Adrenalectomy in Aldosterone-Producing Adenomas: A Prospective Study

Abstract: The aim of the study was to clarify the relationship and the time of aldosterone and renin recoveries at immediate and long-term follow-up in aldosterone-producing adenoma (APA) patients who underwent adrenalectomy. Prospective and longitudinal protocol in a cohort of APA patients was followed in a single center. Among 43 patients with primary aldosteronism (PA), thirteen APA patients were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Recently, Mermejo et al [32] showed that postoperative suppressed renin levels became detectable between fifteen and thirty days after unilateral adrenalectomy in 13 patients with unilateral PA. Evaluating a large cohort of 94 PA patients, we demonstrated that renin levels increased during the first month of adrenalectomy, but renin concentrations became higher when compared to immediate postoperative levels only after 3 months of adrenalectomy.…”
Section: First Week After Surgery 1 Month After Surgery 3 Months Afte...mentioning
confidence: 99%
“…Recently, Mermejo et al [32] showed that postoperative suppressed renin levels became detectable between fifteen and thirty days after unilateral adrenalectomy in 13 patients with unilateral PA. Evaluating a large cohort of 94 PA patients, we demonstrated that renin levels increased during the first month of adrenalectomy, but renin concentrations became higher when compared to immediate postoperative levels only after 3 months of adrenalectomy.…”
Section: First Week After Surgery 1 Month After Surgery 3 Months Afte...mentioning
confidence: 99%
“…Hypoaldosteronism is defined by aldosterone deficiency or resistance and is often referred to as "type 4 RTA." Aldosterone deficiency may be the result of hyporeninism-hypoaldosteronism in patients with diabetes or kidney function impairment; angiotensin inhibitor use, such as angiotensin-converting enzyme inhibitors (ACEis) or angiotensin receptor blockers (ARBs); primary adrenal insufficiency; anticoagulation by heparin [10]; hereditary enzymatic deficiencies such as aldosterone synthase deficiency [11,12] or Gordon's syndrome [13]; a severe illness condition due to adrenocorticotropic hormone (ACTH) hypersecretion, which diverts the substrate to cortisol synthesis [14]; or a transient hypoaldosteronism following surgical treatment of hyperaldosteronism [15]. Aldosterone resistance is usually iatrogenic due to the administration of potassium-sparing diuretics [16] or antibiotics such as trimethoprim [5,6] or pentamidine [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoaldosteronism is de ned by aldosterone de ciency or resistance and is often referred to as "type 4 RTA." Aldosterone de ciency may be the result of hyporeninism-hypoaldosteronism in patients with diabetes or kidney function impairment; angiotensin inhibitor use such as ACEi or ARB; primary adrenal insu ciency; anticoagulation by heparin [12]; hereditary enzymatic de ciencies such as aldosterone synthase de ciency [13,14] or Gordon's syndrome [15]; severe illness condition due to adrenocorticotropic hormone (ACTH) hypersecretion, which diverts the substrate to cortisol synthesis [16]; or a transient hypoaldosteronism following a surgical treatment of hyperaldosteronism [17].…”
mentioning
confidence: 99%